VD_FINDINFO HC / 2020 / 201 vom 5. März 2020 - VD Tribunal cantonal (2020)
ILLICÉITÉ, ASSISTANCE JUDICIAIRE, MOTIF DE RÉVISION, TRANSACTION JUDICIAIRE | 285 al. 2 CC, 117 let. b CPC (CH), 121 CPC (CH), 328 CPC (CH)